Effects of landscape and habitat quality on Orthoptera assemblages of pre-alpine calcareous grasslands - Löffler, Franz; Fartmann, Thomas (Agriculture, ecosystems & environment, 2017)
•Traditional low-intensity land use favours Orthoptera diversity and abundance.•Orthoptera diversity and abundance peak in young grassland fallows.•Habitat heterogeneity increases Orthoptera diversity in calcareous grasslands.•Habitat connectivity is less important for Orthoptera diversity.•Conservation should focus on improving habitat heterogeneity and habitat quality. Due to the transition from traditional land use to modern agriculture throughout Europe, semi-natural grasslands are subject to severe environmental changes. Both agricultural intensification and abandonment have caused degradation, loss and fragmentation of semi-natural grasslands with adverse effects on biodiversity. We analysed the effects of landscape and habitat quality on Orthoptera in pre-alpine calcareous grasslands of the Northern Limestone Alps. At the landscape level, we focused on the effects of functional connectivity, patch size and habitat heterogeneity on Orthoptera species richness of 13 randomly selected grassland patches. At the habitat level, we studied the effects of land use on vegetation structure and microclimate as well as on Orthoptera species richness and abundance on 50 randomly chosen plots within these patches. At the landscape level, the number of Orthoptera species in well-connected pre-alpine calcareous grasslands increased with habitat heterogeneity, which was inter-related with patch size. Functional connectivity, however, had no effect on species richness. At the habitat level, species richness and abundance of Orthoptera were driven by land use together with vegetation structure and microclimate. In general, the explanatory power of our abundance models was at least twice as high as those of the species richness models. Based on the results of our study, conservation management of grassland Orthoptera should primarily focus on improving habitat heterogeneity and habitat quality within patches.